Quality of Ground Waters in Bikaner District of Western Rajasthan - Gajbhiye, K S; Kolarkar, A S; Bhatia, O P (Annals of Arid Zone, 2016)
The quality of ground waters in Bikaner district of western Rajasthan has hen studied on the basis analysis of 137 representative samples. Waters are mostly saline to highly saline in nature with BC in the range of 533 to 21500 micromhos/cm. They have generally a marked concentration of chloride. chiefly of sodium. In general, in waters of salinity below 2250 micromhos/cm, calcium is more than magnesium whereas reverse is generally the case in very high saline waters. (BC above 2250 micromhos/ cm). The value of S.A.R. ranges from 0.64 to 56.11 and 33.58 per cent of waters fall under high to very high S.A.R. classes. The content of boron is not an any acute problem; and its distribution is significantly correlated with EC and S.A.R.